Fatherhood as a Spatial-Contextual Phenomenon: Israeli Gay Fathers through Surrogacy. (October 2021) - Tsfati, Maya; Nadan, Yochay; Biton, Netanel; Serdtse, Yan
This study aims to explore the experiences and accounts of Israeli gay fathers through surrogacy, with regard to contextual elements in general and geographical location in particular. Fourteen Jewish-Israeli gay fathers who became parents through surrogacy abroad were interviewed. Half of the participants live in Tel Aviv, and the other half live in the country's outlying areas in villages or relatively small towns. In-depth semi-structured interviews were conducted, recorded, transcribed, and thematically analyzed. The analysis yielded three themes: (a) between "periphery" and "center, " which reflects a spatial binary as expressed in the fathers' accounts; (b) realms of belonging, which focuses on the challenge the fathers pose to the binary periphery/center distinction; and (c) movement toward inclusion, which explores the fathers' constant movement toward belonging within the different spatial realms. Our findings represent fatherhood as a spatial-contextual phenomenon.